Faktor-Faktor yang Mempengaruhi Minat Siswa Melanjutkan Pendidikan Tinggi Ke Universitas Terbuka (Studi Kasus SLTA Negeri dan Swasta Sederajat di Provinsi Jambi) - Mahyudin Mahyudin (Jurnal Ilmiah Dikdaya, 2019)
This study aims to determine whether the factors that influence high school students to the Open University (public and private high school case studies are as well as Jambi Province). The population of this study is the technique used in research to help public and private high school students in Jambi Province, higher education to the Open University in this study using cluster sampling technique. With a method where no sample is available, each unit of the group is in a group / cluster, in this case the regencies and cities in Jambi Province as clusters. Then each district and city is selected in 3 simple random schools and given 10 samples from each -something of each school. The number of samples is 330. The sample unit is high school / high school students or equivalent in class XII. Data analysis method used for respondents is descriptive analysis. The data used to determine the factors that influence students' interest in Higher Education to Open University (Case Study of State and Private High Schools in Jambi Province) using SPSS 18 software. The analysis was conducted to determine the number of respondents in this study. Respondents used were parents, parents of students, parents, parents, parents, residence of students, teachers, college people, driving factors, and report card grades. Logistic regression analysis uses explanatory variables that can be categorical variables or numerical variables that aim to identify the probability of occurrence of variable response categories (Firdaus, Rahmini, Farid, 2011). Hosmer, David W. and Lemeshow, Stanley (2000) show that the vector x '= (x1, x2, ..., xp) denotes as many variables as possible. P (Y = 1 x) = π (x) is a chance that the non-independent variable states the event (y = 1).